Elevated expression of odorant receptors and odorant-binding proteins genes detected in antennae of Culex quinquefasciatus field females - Santos, Suzane Alves; Romão, Tatiany Patricia; Helvecio, Elisama; Barbosa, Rosangela Maria Rodrigues; Leal, Walter Soares; Ayres, Constância Flávia Junqueira (Frontiers in Tropical Diseases, 2022)
Culex quinquefasciatus is responsible for the transmission of filarial worms and several arboviruses. Olfaction plays a crucial role in disease transmission as it influences behaviors that are essential for the survival and reproduction of the mosquito, such as the host-seeking behavior, courtship, and oviposition. Understanding the molecular events that coordinate how mosquitoes find their host may lead to alternative methods to reduce diseases transmission. Our aim was to investigate the differential expression profile of odorant receptor (ORs) and odorant-binding proteins (OBPs) genes in Cx. quinquefasciatus field females compared with CqSLab laboratory mosquito colony. Seventeen genes of interest were evaluated for their qualitative and specific expression by RT-PCR on RNAs extracted from female antennae, female legs, complete male bodies, incomplete female bodies (no head and no legs), and L4 larvae. The general expression mapping of olfactory genes revealed that all analyzed genes were expressed in antennae. Some genes showed different qualitative expression profiles, such as CquiOR2, CquiOR64, CquiOR93, CquiOBP11, and CquiOBP16, which were expressed exclusively in female antennae. On the other hand, CquiOR37, CquiOBP2, and CquiOBP43 are expressed in all sample types, and CquiOBP10 was expressed in female antennae and legs and in the complete male bodies. The expression of CquiOBP5 was detected in the female’s antennae and body, but it was absent in the legs. The quantitative differential expression analysis of six of the 17 genes by RT-qPCR was performed from RNA samples from antenna pools collected in three physiological states, post-emergence, post-mating, and post-blood feeding of the field females and CqSLab. A total of 3,600 antennae were analyzed, in pools containing 100 pairs. Most genes screened showed a higher expression level in field mosquitoes when compared with the laboratory strain CqSLab. The expression of CquiOBP5 and CquiOBP10 genes was significantly different between the post-mating and post blood-meal samples of laboratory females (p < 0.05). Our results suggest specialization of the function of the genes studied and divergence in the expression pattern of field mosquitoes compared with laboratory mosquitoes, and therefore, caution should be exercised in the interpretation of data from laboratory mosquito studies.